Analisis Perubahan Berat Badan Balita dengan Estimator Penalized Spline Kuadratik - Muhammad Jayzul Usrah; Anna Islamiyati; Anisa (Hasanuddin University, 2022)
Nonparametric regression is a regression approach that is used when one of the parametric assumptions are not fulfilled. One of the estimators in nonparametric regression is penalized spline. The growth pattern of toddler that varied each month of observation make the suitable regression approach is nonparametric penalized spline regression because of its high flexibility. This study aims to obtain an estimate of the growth model for toddler in South Sulawesi. The optimal model obtained with a minimum GCV value of 4.87E-05 using two point knots that is 14 and 56 with lamda 100. The estimation results show that there are 3 intervals of change patterns in the growth of toddler in South Sulawesi